Biglycan Intensifies ALK5–Smad2/3 Signaling by TGF‐β1 and Downregulates Syndecan‐4 in Cultured Vascular Endothelial Cells. Issue 5 (10th January 2017) - Hara, Takato; Yoshida, Eiko; Shinkai, Yasuhiro; Yamamoto, Chika; Fujiwara, Yasuyuki; Kumagai, Yoshito; Kaji, Toshiyuki
ABSTRACT: Proteoglycans are macromolecules that consist of a core protein and one or more glycosaminoglycan side chains. A small leucine‐rich dermatan sulfate proteoglycan, biglycan, is one of the predominant types of proteoglycans synthesized by vascular endothelial cells; however, the physiological functions of biglycan are not completely understood. In the present study, bovine aortic endothelial cells in culture were transfected with small interfering RNAs for biglycan, and the expression of other proteoglycans was examined. Transforming growth factor‐β1 signaling was also investigated, because the interaction of biglycan with cytokines has been reported. Biglycan was found to form a complex with either transforming growth factor‐β1 or the transforming growth factor‐β1 type I receptor, ALK5, and to intensify the phosphorylation of Smad2/3, resulting in a lower expression of the transmembrane heparan sulfate proteoglycan, syndecan‐4. This is the first report to clarify the function of biglycan as a regulatory molecule of the ALK5–Smad2/3 TGF‐β1 signaling pathway that mediates the suppression of syndecan‐4 expression in vascular endothelial cells. J. Cell. Biochem. 118: 1087–1096, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Biglycan intensifies TGF‐β1–ALK5–Smad2/3 signaling pathway that mediates the suppression of syndecan‐4 expression in vascular endothelial cells.